Energy detection based spectrum sensing - Quek, Aubrey Ting (2017)
Wireless communication forms the bulk of today’s communication between humans to humans, humans to machine, and machine to machine interaction. As technology advances, the reliance on wireless technology increase to accommodate the need for fast information relays and work efficiency. The data that transmit wirelessly uses the Electromagnetic spectrum space to travel between devices. The spectrum being seen as a national property is sectioned up and licensed to different users and organizations under the government discretion. Due to this allocation system, the spectrum is not utilized efficiently. This under-utilization problem, have brought about cognitive radio communications to emerge as a reliable and effective solution. The spectrum sensing problem has gained new aspects with cognitive radio and opportunistic spectrum access concepts. This project focuses on the spectrum sensing detection for interweave cognitive radio networks. Effective spectrum sensing will allow secondary users to use the spectrum while primary users are inactive. This will ensure efficient use of the spectrum while not violating the rights of the primary users. In this project, the energy detection technique was employed to investigate its accuracy against its low complexity algorithm. The detection performance can be enhanced by incorporating other sensing techniques to compensate for the energy detector limitations. This paper will raise awareness of the importance of the spectrum space as well as the need for further research on spectrum sensing techniques.